Implementation - Moustafa Abdel Kader; Nasr Mohamed M. Osman (The Egyptian Journal of Radiology and Nuclear Medicine, 2016)
Objective: To evaluate the role of color Doppler sonography in comparison with CXR and CT imaging in diagnosis of pneumonia in adults. Patients and methods: Thirty-one patients with clinical suspicion of pneumonia were assessed by chest radiography, CT and sonography. Quantitative and qualitative sonographic examination of lesions was performed using color Doppler imaging. The correlation between color Doppler and CT findings was determined. Results: Lung ultrasound showed high sensitivity (100%), specificity (93.8%) and diagnostic accuracy 96.8% in diagnosis of pneumonia. It detected air bronchogram in all cases, simple effusion in 18 cases and effusion with internal echoes in 8 cases. It was almost agreement with CT findings (K = 0.93). The sensitivity of chest X-ray was low (60%). It was moderate agreement with CT findings (K = 0.608). A significant changes were seen in flow pattern in comparison with severity of necrosis by CT (P value = 0.038). Majority of our cases reflected pulmonary arterial flow pattern that was found in 21 cases. Conclusion: Lung ultrasound with color Doppler imaging is highly accurate and valid alternatively in diagnosis of pneumonia. By qualitative and quantitative impedance measurement, pulmonary and bronchial arteries can be differentiated. The flow pattern of pulmonary arteries was an indicative of good outcome.